2019
DOI: 10.1038/s41467-018-08183-w
|View full text |Cite
|
Sign up to set email alerts
|

tACS motor system effects can be caused by transcutaneous stimulation of peripheral nerves

Abstract: Transcranial alternating current stimulation (tACS) is a noninvasive neuromodulation method which has been shown to modulate hearing, motor, cognitive and memory function. However, the mechanisms underpinning these findings are controversial, as studies show that the current reaching the cortex may not be strong enough to entrain neural activity. Here, we propose a new hypothesis to reconcile these opposing results: tACS effects are caused by transcutaneous stimulation of peripheral nerves in the skin and not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
188
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(199 citation statements)
references
References 66 publications
7
188
2
2
Order By: Relevance
“…Stimulation of peripheral nerves in the skin might induce rhythmic activation in the somatosensory cortex. Cutaneous stimulation effects have been shown to largely explain tACS effects on motor cortex, however, it is unclear whether this explanation can be generalized to stimulation effects beyond motor cortex (31). In a recent study by our group, Schwab et al (46) addressed this point by source analysis of neural effects induced by tACS over the parieto-occipital cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of peripheral nerves in the skin might induce rhythmic activation in the somatosensory cortex. Cutaneous stimulation effects have been shown to largely explain tACS effects on motor cortex, however, it is unclear whether this explanation can be generalized to stimulation effects beyond motor cortex (31). In a recent study by our group, Schwab et al (46) addressed this point by source analysis of neural effects induced by tACS over the parieto-occipital cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Further insight has been provided primarily in the motor domain, by showing tACS-phase-dependent changes in cortical excitability as measured by concurrent motor evoked potentials (24)(25)(26) or tACSinduced enhancement and phase cancellation of peripheral tremor in healthy subjects and patients with Parkinson's disease using closed-loop protocols (27)(28)(29)(30). Yet, latest findings by Asamoah et al (31) revealed that tACS-effects on the motor cortex are dominated by cutaneous stimulation of peripheral nerves in the skin leading to rhythmic activation of the sensorimotor system rather than by transcranial modulation of cortical tissue. Thus, evidence for phasespecific neural effects of tACS in the motor domain might not necessarily be generalizable to transcranial entrainment effects in cortical regions apart from the motor cortex.…”
Section: Introductionmentioning
confidence: 99%
“…While positive results in published studies provide evidence of causality, it remains important to optimize our methods if we to demonstrate causality beyond reasonable doubt: Otherwise any subsequent failure to replicate might be mistakenly interpreted as an absence of a causal role of these mechanisms on underlying neural processes (e.g., speech perception). Furthermore, concerns have already been raised concerning analytic methods used in existing studies (e.g., Asamoah et al, 2019a), and the possibility of peripheral effects of electrical stimulation (e.g., Asamoah, Khatoun, & Mc Laughlin, 2019b).…”
Section: Methodological Implicationsmentioning
confidence: 99%
“…Kleinert, Szymanski, & Müller (2017) also reported that participants are unable to determine whether frontal and parietal regions were stimulated in-or out-of-phase from each other. Nevertheless, a recent study convincingly demonstrated that some tACS effects on the motor system can be explained by stimulation of peripheral nerves (Asamoah et al, 2019b). It is possible that this issue could also affect stimulation of the auditory system, which needs to be addressed in future work.…”
Section: Limitations and Future Directionsmentioning
confidence: 96%
“…This neural tracking is linked to speech processing: neural tracking is stronger when sentences are intelligible (Peelle, Gross, and Davis 2013;Ding and Simon 2013) and indicates how the speech signal is parsed in the brain (Kösem et al 2018;Ding et al 2016;Ten Oever and Sack 2015). tACS is thought to influence neural tracking by modulating oscillatory activity of neural networks (Fröhlich and McCormick 2010;Witkowski et al 2016;Thut, Schyns, and Gross 2011) (but see (Asamoah, Khatoun, and Mc Laughlin 2019)), and hence may provide a technique to test for a causal influence of neural tracking on the comprehension of spoken language. So far, most tACS studies on speech have focused on effects of tACS phase, that is, how the temporal alignment of the tACS current and speech envelope affect speech comprehension.…”
Section: Introductionmentioning
confidence: 99%